Biomechanical Measurement of Rabbit Cornea by a Modified Scheimpflug Device. (3rd July 2016) - Zhang, Bo; Gu, Jianjun; Zhang, Xiaoxiao; Yang, Bin; Wang, Zheng; Zheng, Danying
Abstract : Purpose . To explore the probability and variation in biomechanical measurements of rabbit cornea by a modified Scheimpflug device. Methods . A modified Scheimpflug device was developed by imaging anterior segment of the model imitating the intact eye at various posterior pressures. The eight isolated rabbit corneas were mounted on the Barron artificial chamber and images of the anterior segment were taken at posterior pressures of 15, 30, 45, 60, and 75 mmHg by the device. The repeatability and reliability of the parameters including CCT, ACD, ACV, and CV were evaluated at each posterior pressure. All the variations of the parameters at the different posterior pressures were calculated. Results . All parameters showed good intraobserver reliability (Cronbach's alpha; intraclass correlation coefficient, α, ICC > 0.96) and repeatability in the modified Scheimpflug device. With the increase of posterior pressures, the ratio of CCT decreased linearly and the bulk modulus gradually reduced to a platform. The increase of ACD was almost linear with the posterior pressures elevated. Conclusions . The modified Scheimpflug device was a valuable tool to investigate the biomechanics of the cornea. The posterior pressure 15–75 mmHg range produced small viscoelastic deformations and nearly linear pressure-deformation response in the rabbit cornea.